Evolutionary conservation of dopamine-mediated cellular plasticity in Arctic sponges (Porifera) - Kravchuk, Oksana I.; Finoshin, Alexander D.; Nikishina, Yulia O.; Melnikova, Victoria I.; Kublanov, Ilya V.; Sutormin, Dmitry A.; Rusanova, Anastasiia N.; Ri, Maxim T.; Isaev, Artem B.; Mikhailov, Kirill V.; Ziganshin, Rustam H.; Adameyko, Kim I.; et al. (Frontiers in Molecular Biosciences, 2025)
Dopamine is an evolutionarily ancient signaling molecule implicated in stress responses across the tree of life. The role of dopamine is well-documented in the nervous system of animals, yet in the early-branching animal lineage of sponges its utility is poorly understood. Arctic marine sponges inhabiting the tidal zone of the White Sea, with fluctuating seasonal ice cover and solute concentrations, exhibit remarkable physiological plasticity, making them ideal models for studying conserved stress-response mechanisms. We investigated the dopamine signaling in two sponge species, Sycon ciliatum (class Calcarea) and Halisarca dujardini (class Demospongiae), using metagenomics, transcriptomics, high performance liquid chromatography, mass spectrometry, molecular docking, and immunofluorescence. S. ciliatum expresses an aromatic amino acid decarboxylase-like enzyme and efficiently converts L-DOPA to dopamine, whereas H. dujardini lacks this canonical biosynthetic enzyme, but accumulates dopamine, likely via its symbionts. During morphogenetic transitions in H. dujardini, genes involved in dopamine turnover, including tyrosinase, dopamine β-hydroxylase, and G protein–coupled receptors (GPCRs), showed dynamic expression. Molecular docking revealed that GPCR affinity for dopamine is modulated by cellular redox status. Notably, we report the first evidence of post-translational dopaminylation of cytoskeleton proteins in a non-bilaterian animal. Fluctuations in cellular dopamine levels and actin dopaminylation correlated with structural remodeling of the aquiferous system throughout the sponge life cycle. These findings demonstrate that dopamine regulates cellular plasticity through both transcriptional and post-translational mechanisms. The discovery of dopaminylation in sponges expands the evolutionary scope of catecholamine signaling and underscores the ancient role of dopamine in the regulatory interactions of animal cells.